COVID-19 Is Distinct From SARS-CoV-2-Negative Community-Acquired Pneumonia - Zhou, Yutian; Guo, Shujin; He, Ye; Zuo, Qiunan; Liu, Danju; Xiao, Meng; Fan, Jinxiu; Li, Xiaohui (Frontiers in Cellular and Infection Microbiology, 2020)
Background: Corona virus disease 2019 (COVID-19) is a respiratory infectious disease and spread rapidly all over the world. Many studies had concluded the clinical features of COVID-19, however, the comparation between older and young patients is still unclear. Moreover, the mortality is correlated with the severity of the disease, and the indicators for severity grading is inexactly. We aimed to analyzed the clinical characteristics of COVID-19 and compared the difference between older and young patients. Methods: Patients diagnosed COVID-19 were enrolled. Clinical, radiological characteristics and laboratory data were analyzed. Results: The average age of the 304 COVID-19 patients was 60.3 years. Of 137 patients were young patients and 167 patients were the older ones. Patients were classified to moderate, severe and critically severe groups. Both young and older patients had clinical manifestations of fever, cough, fatigue, dyspnea and chest distress. Compared with the young patients, the older ones had more chronic diseases, such as hypertension and diabetes. CT imaging features of COVID-19 mainly presented patchy ground glass opacities and the area of the patchy determined the disease severity. Blood examination abnormalities showed decreased level of WBC, lymphocyte, lymphocyte ratio and albumin; and elevated level of CRP, ALT/AST, BUN, LDH, troponin-I and creatinine. There is no difference with these laboratory abnormalities in the older patients and the young ones. Compared to the moderate group, the severe and critically severe groups had significant reduction in lymphocyte and increasing in CRP level, neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR). Conclusion: The older people with chronic diseases are more susceptible to SARS-CoV-2 infection and are more likely to develop severe and critically severe infection. CT imaging presentation, lymphopenia and CRP are important indicators in severity grading of COVID-19. NLR and PLR are important biomarkers for disease severity.